Prevalence of medical writing in hematological malignancy review articles - Héctor A. Vaquera-Alfaro; Elham Nasrollahi; Yashvin Onkarappa Mangala; David Russler-Germain; Aaron Goodman; Ghulam Rehman Mohyuddin (BMC Cancer)
Abstract Background Medical writing services, initially developed to streamline manuscript preparation, have raised ethical concerns due to their association with industry influence and spin. While prevalent in oncology and malignant hematology clinical trials, medical writing involvement in review articles remains underexplored, particularly in the hematology literature. Furthermore, conflict of interests of the writers may also affect the content of review articles. This study investigates the prevalence, characteristics, and funding sources of medical writing in malignant hematology review articles and their relationship with the financial conflicts of interest (CoI) among authors. Methods We conducted a cross-sectional analysis of review articles published in the five-year period between January 2019 and December 2023 in the ten highest-rated hematology journals (by 2023 Journal Citation Report Impact Factor). Inclusion criteria encompassed narrative and systematic reviews, guidelines, and clinical advice articles, excluding studies focused solely on benign hematology or basic science. Results Among 663 included reviews, medical writing involvement was disclosed in 5.7% of articles in which in no instance the medical writer was included as a co-author; with as high as 21% of review articles in a single journal having disclosed medical writing assistance. Medical writers were primarily industry-sponsored (89%). Reviews on plasma cell malignancies had the highest medical writing usage (11%). Direct CoIs were identified in 28% and 34% of first and last authors, respectively, rising to 71% in drug-specific reviews. Only one journal had explicit policies regulating medical writing in reviews. Conclusions Although the prevalence of medical writing in malignant hematology review articles remains low, at least one journal had over 20% of review articles disclosing medical writer usage. Review articles about specific drugs are often written by authors with direct payments from the manufacturer of the drug in question.